Androgen Receptor Survival Signaling Is Blocked by Anti-β2-microglobulin Monoclonal Antibody via a MAPK/Lipogenic Pathway in Human Prostate Cancer Cells - Huang, Wen-Chin (American Society for Biochemistry and Molecular Biology, 2010)
A new cis-acting element, sterol regulatory element-binding protein-1 (SREBP-1) binding site, within the 5′-flanking human androgen receptor (AR) promoter region and its binding transcription factor, SREBP-1, was identified to regulate AR transcription in AR-positive human prostate cancer cells. We further characterized the molecular mechanism by which a novel anti-β2-microglobulin monoclonal antibody (β2M mAb), shown to induce massive cell death in a number of human and mouse cancer cell lines, interrupted multiple cell signaling pathways in human prostate cancer cells. β2M mAb decreased AR expression through inactivation of MAPK and SREBP-1. By inactivation of MAPK, β2M mAb decreased prostate cancer cell proliferation and survival. By inhibition of SREBP-1, β2M mAb reduced fatty acid and lipid levels, an integral component of cell membrane, cell signaling mediators, and energy metabolism. These results provide for the first time a molecular link between the β2M intracellular signaling axis mediated by MAPK and SREBP-1 and involving lipid signaling, which collectively regulates AR expression and function. Antagonizing β2M by β2M mAb may be an effective therapeutic approach simultaneously targeting multiple downstream signaling pathways converging with MAPK, SREBP-1, and AR, important for controlling prostate cancer cell growth, survival, and progression.